2014
DOI: 10.1037/hea0000024
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing benefits of helping others: A randomized controlled trial testing expressive helping to address survivorship problems after hematopoietic stem cell transplant.

Abstract: Peer helping through writing benefits transplant survivors with moderate-severe survivorship problems, but only if they have first completed expressive writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(117 citation statements)
references
References 53 publications
3
113
1
Order By: Relevance
“…Of the 64 included studies, 9,51-58,66-119 59 9,51,[54][55][56][57][58][66][67][68][71][72][73][74][75][76][77][79][80][81][82][83][84][85][86]88,89,91, were RCTs, and four 52,78,87,92 were non-randomised studies. The remaining study 53 was a matched case-control study.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 64 included studies, 9,51-58,66-119 59 9,51,[54][55][56][57][58][66][67][68][71][72][73][74][75][76][77][79][80][81][82][83][84][85][86]88,89,91, were RCTs, and four 52,78,87,92 were non-randomised studies. The remaining study 53 was a matched case-control study.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…The study by Rickett et al 66 is reported in the Facilitated TW section. Here, the studies by Cepeda et al 85 and Rini et al 86 are described. A summary of main characteristics is presented in Table 17.…”
Section: Overviewmentioning
confidence: 96%
See 3 more Smart Citations